Soil CO2 Efflux Response to Combined Application of Adaptation Technologies, Nitrogen Fertilization, and External Carbon Amendment in Wheat and Barley Field - Darenova, Eva; Findurova, Hana; Holub, Petr; Klem, Karel (Frontiers in Environmental Science, 2022)
Agricultural practices applied to increase crop production, and secure future food demands can have a large negative impact on the environmental quality. They should be, therefore, also evaluated in terms of an impact on soil organic carbon (C) content and greenhouse gas emissions. In this study, we investigated the combined effects of adaptation technology (AT) based on no-till crop sowing into cover crop mulch, nitrogen (N) fertilization and external C supply in the form of biochar, compost and composted biochar on soil CO2 efflux (Rs). Rs was measured using a closed gas-exchange system in biweekly to monthly intervals during two consecutive years when winter wheat (1st year) and spring barley (2nd year) were cultivated. Biochar, compost and composted biochar had no significant effects on Rs. N fertilization with the medium fertilizer dose tended to increase Rs compared to the control in the beginning of the growing season, followed with Rs decrease later in the season. On the other hand, fertilization with the maximum fertilizer dose mostly decreased Rs through the whole growing seasons. AT affected the dynamics of Rs substantially, depending on the year, site and N fertilization, resulting in significant interactions between technology and date of measurement and also between site and technology. However, the mean effect of AT across the whole season was insignificant. The results show that the C increase in the soil that occurs after the application of compost and the combination of composted biochar application with AT is not accompanied by an increase in Rs and thus leads to at least short-term C storage in the soil. The reduction of CO2 emissions from soil to the atmosphere under AT represents a positive aspect of such management practice for mitigating climate change..